1999
DOI: 10.1191/096032799678845061
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a carcinogenic aromatic amine from an azo dye by human skin bacteria in vitro

Abstract: Azo dyes represent the major class of dyestuffs. They are metabolised to the corresponding amines by liver enzymes and the intestinal microflora following incorporation by both experimental animals and humans. For safety evaluation of the dermal exposure of consumers to azo dyes from wearing coloured textiles, a possible cleavage of azo dyes by the skin microflora should be considered since, in contrast to many dyes, aromatic amines are easily absorbed by the skin. A method for measuring the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
105
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(112 citation statements)
references
References 14 publications
0
105
0
7
Order By: Relevance
“…Many synthetic azo dyes can be converted to potentially carcinogenic aromatic amines after reduction (Platzek et al, 1999). Because of the widespread use of azo dyes, human intestinal micro-organisms are exposed to these compounds (Hanauer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many synthetic azo dyes can be converted to potentially carcinogenic aromatic amines after reduction (Platzek et al, 1999). Because of the widespread use of azo dyes, human intestinal micro-organisms are exposed to these compounds (Hanauer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…8, inset) which is characteristic of pure PEDOT and confirms its amorphous nature 40 . That peak appears for samples with higher concentration of polymer in composite, PEDOT/ZnO (1-3) and (1)(2)(3)(4)(5). The XRD results show that the increase in the polymer ratio in composite significantly affects the surface of ZnO photocatalyst.…”
Section: Xrd Analysismentioning
confidence: 74%
“…Morphology of pure PEDOT polymers differ among themselves as it is observed that polymers form the aggregated particles. The size of primary particles seems to be larger for PEDOT (1)(2)(3)(4)(5) (Fig. 6c) than that of the other two samples PEDOT (1-2) (Fig.…”
Section: Sem Analysismentioning
confidence: 97%
“…Environmental pollution with dyes can have dire effect on animal, plants, and human health. [4][5][6][7] One of the most important families of dyes is azo dyes that contain −N=N− bond in their structures. 8 So far azo dyes have found many applications.…”
Section: Introductionmentioning
confidence: 99%